2023
DOI: 10.1186/s12348-022-00321-2
|View full text |Cite
|
Sign up to set email alerts
|

Ocular adverse events associated with immune checkpoint inhibitors, a scoping review

Abstract: Introduction Immune checkpoint inhibitors (ICIs) have become an important part of the treatment of multiple cancers, especially for advanced melanoma and non-small cell lung cancer. Some tumors are capable of escaping immunosurveillance by stimulating checkpoints on T-cells. ICIs prevent activation of these checkpoints and thereby stimulate the immune system and indirectly the anti-tumor response. However, the use of ICIs is associated with various adverse events. Ocular side effects are rare b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 210 publications
0
14
0
Order By: Relevance
“…A literature review reveals a paucity of cases detailing Vogt-Koyanagi-Harada (VKH)-like syndrome associated with nivolumab, highlighting the uniqueness of this case. 1 Mechanisms of immune checkpoint inhibitor (ICI)-induced panuveitis, similar to VKH, are thought to involve a T-cell mediated attack on melanocytes, which are present in the uveal tract of the eye, 2 with most cases reported representing adverse ocular events to immunotherapy in the context of metastatic melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…A literature review reveals a paucity of cases detailing Vogt-Koyanagi-Harada (VKH)-like syndrome associated with nivolumab, highlighting the uniqueness of this case. 1 Mechanisms of immune checkpoint inhibitor (ICI)-induced panuveitis, similar to VKH, are thought to involve a T-cell mediated attack on melanocytes, which are present in the uveal tract of the eye, 2 with most cases reported representing adverse ocular events to immunotherapy in the context of metastatic melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…Martens et al (2023) also described a strong discrepancy between anterior and panuveitis, and intermediate uveitis. Among 134 reported cases, they found ICI-induced anterior uveitis accounted for 45%, panuveitis 42% (of which 22% were VKH-like), posterior 4%, and intermediate 6% [128]. A review of uveitis manifestations documented in phase I-III trials showed comparable results [71].…”
Section: Manifestations Of Uveitis Associated With Icismentioning
confidence: 99%
“…Ipi/Nivo work synergistically to enhance host T-cell defenses by inhibiting cytotoxic T-lymphocyte-associated antigen 4 (CTLA4) and programmed cell death protein 1 (PD1), respectively, and are used as first-line therapy for metastatic melanoma [ 3 , 4 ]. Many types of inflammatory ocular adverse events have been reported with Ipi/Nivo combination therapy, including uveitis, retinal inflammation, retinal vasculitis, and Vogt-Koyanagi-Harada-like syndrome [ 5 ]. Furthermore, choroidal involvement with checkpoint inhibitor-related toxicity can present with birdshot chorioretinopathy, choroidal thinning, and choroidal effusions [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many types of inflammatory ocular adverse events have been reported with Ipi/Nivo combination therapy, including uveitis, retinal inflammation, retinal vasculitis, and Vogt-Koyanagi-Harada-like syndrome [ 5 ]. Furthermore, choroidal involvement with checkpoint inhibitor-related toxicity can present with birdshot chorioretinopathy, choroidal thinning, and choroidal effusions [ 5 ]. Herein, we report a novel finding of vitiligo-like loss of pigmentation in the retinal pigment epithelium (RPE) and choroid in a patient with multi-metastatic cutaneous melanoma being treated with ipilimumab and nivolumab.…”
Section: Introductionmentioning
confidence: 99%